Brief Report: Importance of SOX8 for In Vitro Chondrogenic Differentiation of Human Mesenchymal Stromal Cells. (23rd May 2014) - Herlofsen, Sarah R.; Høiby, Torill; Cacchiarelli, Davide; Zhang, Xiaolan; Mikkelsen, Tarjei S.; Brinchmann, Jan E.
Abstract: The transcription factor SOX9 is believed to be the master regulator of chondrogenesis. SOX8 is another SOX group E transcription factor with a high degree of homology to SOX9. Here, we demonstrate that SOX8 mRNA levels decrease during in vitro dedifferentiation of human articular chondrocytes and increase during chondrogenic differentiation of mesenchymal stromal cells. Knockdown of SOX9 reduced the expression of SOX8, COL2A1, and a range of other chondrogenic molecules. SOX8 knockdown reduced the expression of a large number of overlapping chondrogenic molecules, but not SOX9 . Neither siSOX9 nor siSOX8 altered expression of the hypertrophic marker gene COL10A1 . siSOX9, but not siSOX8 led to upregulation of hypertrophy associated genes MMP13 and ALPL . Transfection of synthetic SOX5, 6, and 9 mRNA trio upregulated SOX8, COL2A1, and ACAN, but not COL10A1 mRNA. Replacement of synthetic SOX9 by SOX8 in the SOX trio showed similar but lower chondrogenic effect. We conclude that SOX8 expression is regulated by SOX9, and that both together with SOX5 and SOX6 are required as a SOX quartet for transcription of COL2A1 and a large number of other chondrogenic molecules. Neither SOX8 nor SOX9 affect COL10A1 expression, but SOX9 inhibits chondrocyte hypertrophy through inhibition of MMP13 and ALPL expression. Stem Cells 2014;32:1629–1635